Asymmetric Synthesis of Cyclic Nitrones via Organocatalytic Michael Addition of Aldehydes to Nitroolefins and Subsequent Reductive Cyclization. Issue 9 (24th March 2017) - Szcześniak, Piotr; Staszewska‐Krajewska, Olga; Furman, Bartłomiej; Młynarski, Jacek
Abstract: A direct approach to the synthesis of optically active five‐membered cyclic nitrones is described. The presented strategy is based on organocatalytic Michael addition of aldehydes to trans ‐nitroalkenes and subsequent reductive cyclization. The developed methodology was successfully applied to the asymmetric synthesis of Methdilazine. Abstract : A versatile method for the formation of optically active 5‐membered cyclic nitrones, an attractive building blocks for the stereocontrolled synthesis of bioactive compounds is described. The presented strategy is based on organocatalytic Michael addition of aldehydes to trans ‐nitroalkenes and subsequent Zn‐promoted reductive cyclization process. The developed method opens a flexible pathway for the synthesis of variously substituted nitrones with excellent yields and stereoselectivities. The developed method has been successfully applied in the first asymmetric synthesis of bioactive Methdilazine.